Scaffolding in the Teaching of Writing Discussion Texts Based on SFL Genre-based Approach - Eva Fitriani Syarifah; Wawan Gunawan (University of Kuningan, 2015)
Writing in a second or foreign language seems to be the most difficult language skill for language learners to acquire (Laksmi, 2006; Lestari, 2008; Negari, 2011). Some scholars proposed the implementation of SFL – genre based approach in teaching writing (Derewianka, 1990; Rothery, 1996). However, SFL genre based approach seems to be product or teaching outcomes oriented (Ahn, 2012; Emilia, 2011). Therefore, the concept of scaffolding in which possible supports the process of students‟ individual development is important to be emerged in the teaching stages of SFL – GBA (Bodrova Leong, 1998; Mulatsih, 2011). As a result, This study focuses on the issue of scaffoldings in the teaching of writing discussion texts based on SFL – Genre Based Approach. It particularly aims to investigate how scaffolding processes are implemented in the teaching of writing discussion texts based on SFL-GBA and how they improve the students‟ writing performance. The data rely on teaching and learning process in a classroom with six students in a tertiary level as the focus participants. The method used in the data analysis adopted a qualitative design with reference especially to the theory of the scaffolding and SFL-GBA. The results of analysis show that scaffolding processes are implemented in terms of macro and micro scaffoldings and able to improve the students‟ writing performance specifically in terms of social function, schematic structures, and language features of discussion genre. It is recommended that future related research should be conducted in more diverse of educational settings to see how scaffoldings are implemented in a variety of teaching practices.Keywords: scaffolding, discussion texts, SFL, genre-based approach.